The intersection of global mobility, lifestyle and ELT work: a critical examination of language instructors' trajectories. (4th July 2018) - Codó, Eva
ABSTRACT: This paper examines the intersection of one form of contemporary mobility, i.e. lifestyle mobility, with the ELT industry. It draws on the discursive analysis of a small corpus of life story data produced by native English language teachers of different ages residing in Barcelona. Through their own personal and professional accounts and rationales, it seeks to comprehend how they construct their work experiences in the light of previous professional trajectories, prior expectations and future mobility plans, but also against the backdrop of a highly precarised job market. The article argues that the 'backpacker' language teacher is certainly a reality but also a contemporary cultural myth that works to disguise a complex humanscape of relocators of different ages and aspirations who face difficulties fitting in an industry that expects docile and inexperienced bodies and a local market where nativeness enables quick access to teaching jobs but only to unskilled and temporary ones. The younger informants narrate biographies in flux and a sense of life stagnation or development to which commercial ELT may be differently instrumental. This article challenges assumptions about the value of (native) English in the work field and how easily work experience and qualifications travel around for middle-class professionals.